Diferenças Químicas e Texturais entre os Veios de Quartzo Férteis e Estéreis no Depósito Aurífero Pau-a-Pique (Grupo Aguapeí, Estado de Mato Grosso) - FERNANDES, CARLOS JOSÉ; PULZ, GÊNOVA MARIA; OLIVEIRA, ALESSANDRO SILVA; LIMA E CUNHA, MARIA DO CARMO; BARBOZA, ELZIO SILVA; PINHO, FRANCISCO EGIDIO; QUADROS, ÁLVARO PIZZATO (Pesquisas em Geociências, 1999)
The quartz veins in the Pau-a-Pique gold deposit hosted in Aguapeí Group metassediments have textural, paragenetic and chemical characteristics that provide prospectives criteria for gold. Gold disseminations occur in the quartz vein system and in the hydrothermal halo. The highest gold grades are within quartz veins that have comb, saccaroidal and replacement textures. The barren veins show ribbon and buck textures. Both fertile and barren veins exhibit a lack of correlation between gold grades and of the other elements (As, Fe, Sc and Ta). This behavior indicates that gold grades might be adequate chemical criteria for distinction between barren and the fertile veins. Gold grains appear associated to martite and oxihydroxides pseudomorphs that replace the ore minerals in veins. The mineral assemblage and textures of the quartz veins, suggest a gold remobilization due to Eh-pH fluctuations related to interaction between the ore and the meteoric solutions.